Uporaba ultrazvočne metode za oceno vezanja materialov s cementnih vezivom - Trtnik, Gregor (Gradbeni vestnik, 2009)
In this paper, the possibility of using two different ultrasonic (US) methodsto estimate the initial setting time of different cement based materials is briefly discussed. In the case of different concrete mixtures, an ultrasonic wave trans- mission method (USWT) is analyzed and in the case of pure cement pastes, both the USWT and an ultrasonic wave reflection (USWR) methods as well as their combina- tion are discussed. It was found out that in the case of the USWT method, the initial setting time of an arbitrary concrete and cement paste mixtures can be estimated very accurately from the time of the first inflection point of the corresponding velocity (Vp) - time curve. In the case of pure cement pastes, the initial setting time can be also estimated by the time, when the shear wave reflection coefficient (dr) starts to increase rapidly. As an addition, the end of the first phase of the corresponding vp drcurve can be used to define the initial setting process of cement pastes. Repro- ducibility of both methods is shown and statistical analysis of the estimation of the initial setting time of cement pastes with the ultrasonic wave transmission method is discussed.
Keywords: cement; preiskava materiala; ultrazvočne meritve; ultrazvočne metode; veziva